FINANCIAL PERFORMANCE COMPARISON OF MGNREGs BEFORE AND AFTER COVID-19 – A STUDY OF SELECT SOUTH INDIAN STATES - GNYANESWER, Dr. D. (The journal of contemporary issues in business and government, 2023)
The National Backward and rural Employment Guarantee Act (NREGA) were enacted in September 2005. The act came into consideration on2nd February, 2006 and was executed in a proper sequential manner. In phase-I, it was popularised in 200 most backward districts of the nation. The act was executed in all other districts in 2007-08 under phase-II. As per the first target, NREGA was to be extended into total country within the five years. The objective of the research is Evaluating Financial Performance of the MGNREG scheme before and after the covid-19. Methodology of the study, for this study we are selected South Indian States. Result of the study our analysis showed there is increase in total Central Government released funds, material and skilled wages expenditures and average cost per day per Person under the MGNREGS before and after Covid-19. Conclusions of the study showed there is an increase in percentage of funds Utilization, total Expenditures and Wages expenditure under the MGNREGS before and after the covid-19 improves the socio economic status of beneficiaries of the scheme.